Implementasi Makanan Bergizi Untuk Pencegahan Stunting Pada Baduta, Balita, Dan Ibu Hamil Di Kecamatan Berangin - Sari Mariati; Diswanto, Diswanto; Tiara Wulan Dari; Najwa Maharani Vidril; Adham Syahreza; Baihaqi Al Farid (CV. ITTC INDONESIA, 2025)
Stunting is a physical condition in children who experience slow growth and development. This is caused by malnutrition, parenting patterns, infections, and environmental health experienced by pregnant women, as well as toddlers to toddlers. The complexity of the stunting problem begins with the lack of nutritional food consumed during the 1000 days of life from the fetus to the age of two years. The purpose of the study was to socialize healthy nutritious food as an effort to prevent stunting in Berangin District, Sawahlunto Regency. This study uses a qualitative method with data collection techniques through literature studies, observations, interviews with parties involved in preventing stunting, and experiments by conducting a healthy nutritious food cooking demonstration to the Berangin District community. The results of this activity showed an increase in public knowledge about stunting and the application of nutritious food that is easy to consume. Seeing the enthusiasm of the community during the cooking demonstration as a form of implementing healthy nutritious food, it is recommended that health workers in Berangin District can socialize and implement healthy nutritious food that can be consumed as a form of preventing stunting.